Microbiology in action - Heritage, J.; Evans, E. G. V. [ (Emlyn Glyn Vaughn)]; Killington, R. A. (Studies in biology, 1999)
An introductory text providing a broad coverage of the fundamentals of applied microbiology for non-specialists